What are the priorities in basic asthma research? A United Kingdom perspective. - Hallsworth, M; Major, P; Barnes, J; Lee, T (2003)
The National Asthma Campaign (in the United Kingdom) has recently completed a strategic review of priorities for basic asthma research over the next 5 to 10 years. Leading asthma experts and representatives of the main funding agencies were involved in a nationwide consultation. Discussions were carried out in 7 thematic areas: Genetics of asthma, early-life events, environmental influences, immunology and immunotherapy, inflammation and anti-inflammation, airway remodeling, and the interface between academia and industry. Discussions were not restricted by considerations of financial affordability but were driven by vision and science. The consultation highlighted a number of generic issues pertaining to the organization of basic asthma research. Phenotypes of asthma require more robust characterization, particularly for genetic studies. Emphasis on longitudinal studies should be encouraged, and more information can still be gained from existing well-characterized asthma cohorts, though this requires some coordination. Human research is particularly strong and should continue, and the use of human tissue is vital to our understanding of the disease at the cellular and molecular levels. Animal models of asthma remain an important tool with which to dissect disease mechanisms, but they must be improved and refined. The consultation covered a wide range of issues and highlighted the need for collaboration at all levels between research groups and with industry and also between funding agencies. The recommendations made have relevance to everyone involved in basic asthma research. This article describes the recommendations and reviews the specific research issues relating to each of the 7 thematic areas.